Proteções e desproteções de famílias beneficiárias do programa bolsa família: Um olhar a partir do território rural do sertão paraibano. - Silva, Aline Ferreira de Souza (2018)
This study aims to analyze the living conditions and social protection of the beneficiary families of the Bolsa Família Programme in rural area county of Princesa Isabel - backlands of Paraiba. Initially, this search presents the scenario of social protection systems in the international arena and the construction of the Brazilian social protection system with emphasis on social security and public policy of social assistance. Discusses social protection under the hegemony of income security income transfer policies secured by the Social Assistance Policy in this context as well, it presents the design, progress and limits of the main Brazilian Cash Transfer Programmes: Bolsa Família Programme. Focusing on the BFP beneficiary families, we present under the gaze of those situations social protection/defenselessness who experience in their territory.